Knowledge and skills of Emergency Care During Disaster For Community Health Volunteers: A Literature Review - Kamal, Anda; Songwathana, Praneed; Sia, Wipa Sae (Department of Nursing, Faculty of Medicine, Diponegoro University, 2012)
Background: Nowadays, disaster preparedness and responses are essential for everyone to be involved since the disaster becomes increasing. The Community Health Volunteers (CHVs) in particular are the key partners required adequately prepared in emergency care during disaster event. Purpose: The study aims to examine the essential knowledge and skills of emergency care during natural disaster for CHVs. Method: The reviews published during 2000 and 2011 searching from PubMed, Science Direct, CINAHL, ProQuest Medical Library were conducted. Result: Twenty-four articles and documents related to community-based disaster preparedness programs were intensively reviewed. Based on the review, six components of knowledge and skills for emergency care in natural disaster for CHVs are required including 1) early warning, 2) disaster triage, 3) first aid, 4) search and rescue, 5) logistic and communication, and 6) team organizations. Conclusion: There was a few studies focusing on the emergency care in disaster management and some factors related to knowledge and skills were shown. It is therefore recommended that the current CHVs’ knowledge and skills should be explored in order to assist people in their community following disaster event when professional responders are not immediately available to help. Key words: Knowledge, Skill, Community health volunteers, Emergency care, Natural disaster.